Advances in non-intrusive load monitoring for the industrial domain: Challenges, insights, and path forward - Yaniv, Arbel; Beck, Yuval (Renewable & sustainable energy reviews, 2025)
Non-intrusive load monitoring has emerged as an important tool for disaggregating the energy consumption of individual appliances within a facility, relying solely on data from a centralized smart meter. Smart meters have become increasingly predominant in industrial facilities for many reasons, such as regulatory mandates, economic incentives, environmental considerations, and operational advantages. However, the implementation and research of non-intrusive load monitoring specifically for the industrial environment, which is notably complex, are still in their early stages. This study provides a comprehensive overview of the current landscape of non-intrusive load monitoring in the industrial domain, reviews current approaches, identifies existing theoretical and practical challenges unique to the industrial setting, discusses key considerations for non-intrusive load monitoring industrial application development, and highlights the importance of data preprocessing in industrial applications. Additionally, it offers a forward-looking perspective, charting potential avenues for research and innovation. Ultimately, the study aims to provide a holistic view of the subject matter, equipping the reader with a well-rounded perspective that is vital for forming a robust base for subsequent research endeavors. •Review of publications and datasets focused on industrial NILM applications.•Key NILM challenges and guiding principles for industrial applications.•Future directions for NILM in industrial facilities. [Display omitted]